Enhanced water and cooling production from a polygeneration process using biomass: Usefulness of the polygeneration - Kuntal Jana (Next Sustainability, 2025)
Multiple utility production in a single plant is the objective of polygeneration. However, properly designed polygeneration gives the flexibility to change the production rate of utility outputs relatively. This change in utility output production rate may affect the thermodynamic and economic performances of the polygeneration. In many cases, economic parameter may not give same result as thermodynamic parameters. Economic parameter is important to design and measured the acceptability of the plant. In this study ‘usefulness of polygeneration’ is defined to optimize the plant operation. This is an important parameter to find the optimum design parameter from the viewpoint of socio-economics. In this paper, CCGT based polygeneration and ST based polygeneration is simulated by Aspen Plus®. To reduce the operational problem of tar and to increase the flexibility of polygeneration, ST based cycle is explored. Effect of steam generation pressure, steam bleed pressure, and steam bleed amount is shown in this paper. A defined parameter i.e. ‘usefulness of polygeneration’ without and with priority is used to show the importance of the designed polygeneration. Higher the steam generation pressure, increases the usefulness of the polygeneration. With the increase of steam bleed pressure, usefulness with priority decreases and usefulness without priority increases. 20 % steam bleed is the optimum for maximization of usefulness with priority.